Investigating the Pressure Distribution on Uneven Surfaces Using an Educational Robot for Development of Ergonomic School Furniture - Novak, Daniel; Novak, Viktor; Vostinar, Patrik; Volf, Jaromir (Manufacturing Technology Journal, 2024)
The article presents the method of investigating the pressure distribution on uneven surfaces, used for the development of a new, modern series of school furniture that meets the relevant health, pedagogical and legal requirements. During the examination of pressure conditions on school chairs with a flexible tactile sensor, which was primarilly developed for this purpose, exact data on the immediate differences in contact pressures between the person sitting and the seat are obtained. Based on this information, it is then possible to optimally shape the seats during their design and subsequent production according to the age of the sitters and the needs of the organizational form of teaching from the point of view of the specific character of the teaching environment. Technical parameters of the flexible tactile sensor depend on the shape and number of electrodes, as well as on the conductive inks used, they are stated and dis-cussed within the article. Due to the large number of collected data, a robot, otherwise used in teaching, was used for obtaining of individual loading characteristics of the proposed sensor. At the end of the article, the results obtained by the statistical processing of the measurements are summarized and dis-cussed.
Keywords: Teaching process; School chair; Flexible tactile sensor; Pressure distribution; Educational robot